PKM IMPLEMENTASI SIMPAN PINJAM PADA BANK PERKRIDITAN RAKYAT BERBASIS CLIENT SERVER - Sunarmi Sunarmi (Pusat Riset dan Inovasi Nasional, 2022)
Bima Credit and Savings Cooperative Credit Union is a financial institution that provides transaction services to store and borrow money to its members. Bima Savings and Loan Cooperative needs to have an information system to facilitate data processing, carry out tasks appropriately, and minimize errors in recording transactions and financial calculations. To meet the above needs, it is necessary to design a savings and loan information system. The system development method used is SDLC (System Development Life Cycle) which stands for several stages, namely the planning stage, the analysis phase, the design stage, the implementation stage and the maintenance phase, but the maintenance stage is not included in the development of this system. This design uses a programming language that is C # in its creation and mysql as its database. The results of this study are to provide convenience for officers in managing savings and loan data. Desktop-based Savings and Loan Information System, can help to manage, search, make savings and loan reports quickly and easily, and can make savings and loan arrangements and calculate interest directly through the application without being done manually.